Game theory in conjuction with a digitized information retrieval unit - Andalis, Arthur B. (2005)
Game theory is a distinct and interdisciplinary approach to the study of human behavior. The disciplines most involved in game theory are mathematics, economics and the other social and behavioral science. This study aimed to propose the implementation of Game Theory in Information System using the on-line public access catalog (OPAC)The objectives of the study are the following: 1) to determine if there is a connection between categories and data; 2) to prove if the case being studied useful as a conceptual explanation for the process of implementation itself; 3) to know if the theory provide a relevant explanation of actual problems that present itself in consistency while at the same time being consistent with the actual and basic problems presented; 4) to determine if the theory can be modified as conditions change as well as variations of availability of future data ; 5) to determine if the theory present a conceptualization of process, action, and or interaction; and 6) to determine if there is an evident central phenomenon that can be applicable to any theoretical models.